Prevalence and determinants of depression among women with urinary incontinence: a systematic review and meta-analysis worldwide - Sileshi Ayele Abebe; Fanuel Gashaw; Alebachew Tsegaye; Dessie Abebaw; Endeshaw Asaye Kindie; Addisu Minaye Dejen (BMC, 2024)
Abstract Background There is no pooled evidence regarding the prevalence and potential factors associated with depression among women with urinary incontinence worldwide. Hence, a systematic review and meta-analysis were conducted to determine the overall prevalence of depression among urinary incontinent women globally and explore any heterogeneity present. Methods A computerized systematic literature search was performed using the Scopus, PubMed, Embase, Google Scholar, and Snowballing databases. Each database was searched from its start date of March 20, 2023. The study conforms to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. All included articles were published in English and evaluated the prevalence and associated factors of depression among urinary incontinent female patients. Pooled estimations with a 95% confidence interval (CI) were calculated with the DerSimonian‒Laird (DL) random-effects model. Publication bias was evaluated by using funnel plots and statistical tests. Results Our initial electronic database search with the chosen search terms identified 1120 articles in PubMed (35 4), Embase (105), Scopus (325) and Google Scholar (176). The results of the 8 studies reporting a binary outcome using the different validation scales are summarized in the overall prevalence of depression was 18% (95% CI = 11-25%). Unable to read and write (OR: 1.34, 95% CI: [1.01, 1.78], I²= 0%), caesarean delivery (OR: 1.48, 95% CI: [1.30, 1.70], I² = 0%), obesity (OR: 1.37, 95% CI: [1.19, 1.58], I² = 0%), party greater than three (OR: 1.26, 95% CI: [0.98, 1.62], I²= 0%), comorbidity (OR: 1.32, 95% CI: [1.16, 1.49], I² = 85.3%), smoking (OR: 1.58, 95% CI: [0.99, 1.92], I2 = 0%) and single, divorced and widowed (OR: 1.67, 95% CI: [1.45, 1.92], I² = 0%) were the major factors associated with depression. Conclusion and recommendations This review demonstrated the high prevalence of depression among women with urinary incontinence. Being unable to read and write, delivery via caesarean section, obesity, having more than three children, having comorbidities, smoking, being single, being divorced and being widowed were all associated factors. This study identified that there was a strong association between urinary incontinence and depression. Future studies recommend focusing on the causal association between depression and urinary incontinence. PROSPERO Registration numbers of CRD42023418779.